The Invention of a Chair Tradition in Ethiopia: A Case Study of Liminoid Design. (30th June 2020) - Goss, David
Abstract: Both design and invention deal with future materializations, facilitating the environment and artefacts into different categories. These categories are conceptual constructs and any transgression of, combination of, or entering interstices between their imagined conceptual borders is Liminoid Design . Liminoid design is defined in this article as a momentary state of liminality: unstructuredness, transience, inter-categorical or uncategorizable. Though a very common phenomenon, it potentially creates new configurations of reality and new categories in design. This article describes manifestations of liminoid design, through the development of a contemporary Ethiopian chair with the merging of two categories: a side chair with imagery of the historic Aksum stelae. The Aksum stelae are monolithic stone monuments in northern Ethiopia erected during the ancient Kingdom of Aksum (in the early Christian period between the fourth and sixth centuries AD). This amalgamation emphasizes the contemporary connection to the past with a significant moment in Ethiopian history. Though seemingly traditional, this article identifies these chairs as a newly invented design type—the Aksum chair . During several visits to Ethiopia, I visited furniture workshops in Addis Ababa and Aksum and visited purchasers of the chairs as well. This helped the research to trace the proliferation and initiation of an invented traditional style.